Marsdenia tenacissima enhances immune response of tumor infiltrating T lymphocytes to colorectal cancer - Yi, Ben; Zhang, Shuai; Yan, Suying; Liu, Yanfei; Feng, Zhiqiang; Chu, Tianhao; Liu, Jun; Wang, Wei; Xue, Jun; Zhang, Chunze; Wang, Yijia (Frontiers in Immunology, 2023)
Introduction: Tumor-infiltrating T lymphocytes in the tumor microenvironment are critical factors influencing the prognosis and chemotherapy outcomes. As a Chinese herbal medicine, Marsdenia tenacissima extract (MTE) has been widely used to treat cancer in China. Its immunoregulatory effects on tumor-associated macrophages is well known, but whether it regulates tumor-infiltrating T-cell functions remains unclear. Method: We collected 17 tumor samples from MTE-administered colorectal cancer patients, 13 of which showed upregulation of CD3+/CD8+ tumor-infiltrating T cells. Further in vitro and in vivo experiments were performed to investigate the regulatory effects of MTE on tumor-infiltrating T cells and immune escape of tumors. Results: Under single and coculture conditions, MTE inhibited TGF-β1 and PD-L1 expression in the colorectal cancer (CRC) cell lines HCT116 and LoVo. In Jurkat cells, MTE inhibited FOXP3 and IL-10 expression, increased IL-2 expression, but had no effect on PD-1 expression. These findings were confirmed in vitro using subcutaneous and colitis-associated CRC mouse models. MTE also increased the density of CD3+/CD8+ tumor-infiltrating T cells and exhibited considerable tumor-suppressive effects in these two tumor mouse models. Conclusions: Our findings suggested that MTE inhibits the immune escape of cancer cells, a precipitating factor increasing the immune response of T lymphocytes.